2018
DOI: 10.1103/physreva.97.013419
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of optical pumping in the presence of spin-exchange relaxation

Abstract: We have performed quantitative measurements of the variation of the on-resonance absorption coefficients κ 0 of the four hyperfine components of the Cs D 1 transition as a function of laser power P , for pumping with linearly and with circularly polarized light. Sublevel populations derived from rate equations assuming isotropic population relaxation (at a rate γ 1) yield algebraic κ 0 (P) dependences that do not reproduce the experimental findings from Cs vapor in a paraffin-coated cell. However, numerical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…We conclude that an accurate description of the population's redistribution process in the ground state including spin-exchange (as for example in Ref. [44]) as well as the influence of the B 1 field is required for a more precise prediction of the line shapes.…”
Section: The Non-linear Zeeman Splittingmentioning
confidence: 88%
“…We conclude that an accurate description of the population's redistribution process in the ground state including spin-exchange (as for example in Ref. [44]) as well as the influence of the B 1 field is required for a more precise prediction of the line shapes.…”
Section: The Non-linear Zeeman Splittingmentioning
confidence: 88%
“…We compare the experimental results to those obtained with LPL and CPL. In a recent publication [3] we have studied optical pumping in a paraffin-coated Cs vapor cell, in which spin relaxation is dominated by anisotropic (F -and m-dependent) spin-exchange collisions. The measured quantities were the resonant absorption coefficients' dependence on laser power, κ 0 (P ), for the four Cs D 1 hyperfine transitions.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In that paper we have also shown that under the assumption of isotropic relaxation, one can derive algebraic expressions for the κ 0 (P ) dependencies. Here we put these analytical results on the experimental test bench, by repeating the same experiments as described in reference [3] in an uncoated cell, which fulfills the condition of isotropic relaxation at room temperature.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such sensors, atomic spin polarization is created using optical pumping [4,5] and its change due to the interaction with the magnetic field is monitored by optical means. Most commonly, the sensors monitor vector spin polarization (spin orientation), which is created with circularly polarized pumping light [6] and precesses in the magnetic field with the Larmor frequency ω L = γ |B|. In this study we focus on 133 Cs atoms in the ground state with the overall atomic spin F = 4.…”
Section: Introductionmentioning
confidence: 99%